2009
DOI: 10.1111/j.1364-3703.2009.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

RNAi‐mediated resistance to Potato spindle tuber viroid in transgenic tomato expressing a viroid hairpin RNA construct

Abstract: Because of their highly ordered structure, mature viroid RNA molecules are assumed to be resistant to degradation by RNA interference (RNAi). In this article, we report that transgenic tomato plants expressing a hairpin RNA (hpRNA) construct derived from Potato spindle tuber viroid (PSTVd) sequences exhibit resistance to PSTVd infection. Resistance seems to be correlated with high-level accumulation of hpRNA-derived short interfering RNAs (siRNAs) in the plant. Thus, although small RNAs produced by infecting v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(85 citation statements)
references
References 49 publications
2
75
2
4
Order By: Relevance
“…Infection by viroids from both families occurs with the accumulation of 21-to 24-nt viroid-derived small RNAs (vd-sRNAs) with the characteristic properties of the siRNAs associated with RNA silencing, as revealed by RNA gel blot hybridization (5,36,43,46,47,59,74), low-scale sequencing (35,41,44,77), and deep sequencing (17,52). Moreover, mechanically codelivered or agroinoculated dsRNAs interfere with viroid infection in a sequence-specific manner (as also do, at least in one case, in vitro-generated homologous vd-sRNAs codelivered mechanically) (5).…”
mentioning
confidence: 99%
“…Infection by viroids from both families occurs with the accumulation of 21-to 24-nt viroid-derived small RNAs (vd-sRNAs) with the characteristic properties of the siRNAs associated with RNA silencing, as revealed by RNA gel blot hybridization (5,36,43,46,47,59,74), low-scale sequencing (35,41,44,77), and deep sequencing (17,52). Moreover, mechanically codelivered or agroinoculated dsRNAs interfere with viroid infection in a sequence-specific manner (as also do, at least in one case, in vitro-generated homologous vd-sRNAs codelivered mechanically) (5).…”
mentioning
confidence: 99%
“…Thus, transgene anti-sense induced RNA silencing was not inhibited in potato plants at low temperature (Sos-Hegedus et al, 2005). Moreover, tomato plants carrying an IR construct derived from Potato spindle tuber viroid (PSTVd) sequences and exhibiting resistance to PSTVd infection, did not show an elevated IR-siRNA accumulation at 31°C in comparison to 21°C (Schwind et al, 2009). In a more recent study, transgenic tobacco plants transformed separately with IR constructs corresponding to sequences of TMV movement protein gene or CMV replication protein gene, exhibited at both 15°C and 24°C similar high levels of resistance to TMV or CMV, respectively (Hu et al, 2011).…”
Section: Wwwintechopencommentioning
confidence: 97%
“…However, 'traditional' genetic sources of resistance to viruses are rare (Lecoq et al, 2004) and due to the high rate of mutation of the viral genomes this resistance even when applicable, is frequently broken under field conditions. The era of Agrobacterium-mediated genetic transformation of plants which started at the 80s (Thomashow et al, 1980;Zambryskiet al, 1980) offered new promising prospects for engineered genetic resistance to viruses with numerous following studies reporting a successful use of the transgenic technology against almost all genera of plant viruses or even viroids (Lin et al, 2007;Prins et al, 2008;Ritzenthaler, 2005;Schwind et al, 2009). However, mainly due to public concerns for the safety of using transgenic plants in agriculture only in a relatively small number of virus diseases transgenic technology has been used in the field and in these cases it was proved an efficient and safe way of control (Fuchs et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Schwind et al (2009) have even shown that using hpRNA construct in Solanum lycopersicum (tomato) against Potato Spindle Tuber Viroid (PSTVd) produce PSTVd-resistant tomato plant varieties.…”
Section: Virus Resistancementioning
confidence: 99%